Antibacterial Activity of Medicinal Plant (Centauraea Calcitrapa) against Multi-Drug Resistant Bacteria (MDRB) - Moghannem, Saad AM; El-Sherbiny, Gamal M; Sharaf, Mohammed H (The Asia Journal of Applied Microbiology, 2016)
The present study was conducted to evaluate the antibacterial activity of Centauraea calcitrapa against multidrug resistant bacteria (Staphylococcus aureus, Enterococcus faecium, klebsiella pneumoniae, Acinetobacter baumanni, Enterobacter cloacae and Pseudomonas aeruginosa) , purify and identify the active compounds. A sensitivity test was performed using disc diffusion method that resulted in the appearance of multiple drug resistance phenotypes of tested bacteria. Antibacterial activity of Centauraea calcitrapa showed that inhibition zone diameter against Staphylococcus aureus (23mm), Enterococcus faecium (17mm) , Klebsiella pneumoniae (15mm), Acinetobacter baumanni (22mm), Enterobacter cloacae (20mm) and Pseudomonas aeruginosa (18mm) . Highest activity was exhibited against Staphylococcus aureus and can be considered to be more effective than the most commercial antibiotics. The active compound was purified using column chromatography and visualized using thin layer chromatography (TLC). The Minimum inhibitory concentration (MIC) values of active purified compound ranged from 15.6 to 62.5μg/ml. Minimum bactericidal concentrations (MBC) values were two-fold higher than the corresponding MIC values ranged from 31.25 to 125μg/ml. The active purified compound was partial identified using UV, IR, 1HNMR and mass spectroscopy. The analysis of data obtained indicated that; the purified active compound belongs to janerin group of chemical compounds. (Centauraea calcitrapa) is a new source for discovery of bio-active compound against (MDRB).